Impact of Interdisciplinary Team Care for Children With 22q11.2 Deletion Syndrome. (December 2020) - Hickey, Scott E.; Kellogg, Brian; O'Brien, Meghan; Hall, Courtney; Kirschner, Richard E.; Santoro, Stephanie L.; Leonard, Hayley; Baylis, Adriane L.
Objective: To evaluate disease-specific guideline adherence among children with 22q11.2 deletion syndrome receiving multidisciplinary team care through a 22q specialty clinic compared to children not receiving team care. Design: Retrospective chart review; quality improvement project. Setting: Tertiary care pediatric hospital. Patients: One hundred eighty-nine patients with 22q11.2 deletion syndrome were categorized into those receiving team care and those not receiving team care. Guideline adherence was compared between the 2 groups. Main Outcome Measure(s): Percent adherence across 8 disease-specific guidelines. Results: A Welch t test revealed mean adherence among patients receiving team care was significantly higher (83% vs 42%, P < .001) compared those not receiving team care. Among team patients with a single 22q Center visit, a paired samples t test showed that mean adherence increased from 63% before the clinic encounter to 86% six months after the encounter ( P < .001). Some guidelines were more likely to be associated with provider nonadherence, whereas others were more likely to be associated with patient nonadherence. Conclusions: Multidisciplinary team care is associated with significantly higher guideline adherence in children with 22q11DS. Additional research is needed to investigate the effect of team care on long-term health outcomes in children with 22q11DS.